2015
DOI: 10.1016/j.ibmb.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chitin-binding proteins from Manduca sexta provides new insights into evolution of peritrophin A-type chitin-binding domains in insects

Abstract: In insects, chitin is a major structural component of the cuticle and the peritrophic membrane (PM). In nature, chitin is always associated with proteins among which chitin-binding proteins (CBPs) are the most important for forming, maintaining and regulating the functions of these extracellular structures. In this study, a genome-wide search for genes encoding proteins with ChtBD2-type (peritrophin A-type) chitin-binding domains (CBDs) was conducted. A total of 53 genes encoding 56 CBPs were identified, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 50 publications
1
66
2
Order By: Relevance
“…A few genes from A. pisum , A. mellifera , and P. humanus could not be clearly grouped within any of the 16 CPAP1 branches and were left unclassified. It should be noted that although both our analysis (this report and Tetreau et al ., 2014, this issue) and that of Ioannidou et al . (2014) independently verified the close relationship of the new members of the CPAP1 group to the original ten genes described previously for T. castaneum , the presence of the encoded proteins in the cuticle must still be established (and hence are they truly cuticle proteins).…”
Section: Resultscontrasting
confidence: 39%
See 2 more Smart Citations
“…A few genes from A. pisum , A. mellifera , and P. humanus could not be clearly grouped within any of the 16 CPAP1 branches and were left unclassified. It should be noted that although both our analysis (this report and Tetreau et al ., 2014, this issue) and that of Ioannidou et al . (2014) independently verified the close relationship of the new members of the CPAP1 group to the original ten genes described previously for T. castaneum , the presence of the encoded proteins in the cuticle must still be established (and hence are they truly cuticle proteins).…”
Section: Resultscontrasting
confidence: 39%
“…Since similar work had not yet been performed for B. mori , we named the M. sexta genes based on orthology to T. castaneum and homologous genes in other insects. This analysis is described in a companion paper detailing the different groups of proteins containing peritrophin A-type chitin-binding domains in M. sexta (Tetreau et al ., 2014, this issue) but will be summarized here. M. sexta has orthologs to 9 of the 10 CPAP1 genes in T. castaneum with 1-E being the exception.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In nature, CBPs are the major group of proteins that associate with chitin and participate in the formation, maintenance, and regulation of the functions of these extracellular structures (42). Other classes of CBPs function as lectins and chitinases (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…But every other protein known to bind chitin had cysteine residues, and our earlier amino acid studies and work by others had found almost no cysteine in CPs (1,57). Exceptions to this are now known (24,25,40). During that dinner, we arranged that Rebers should spend a sabbatical in my lab testing whether the Consensus binds to chitin.…”
Section: Looking At Sequencesmentioning
confidence: 97%